Pelatihan Mencampur Warna dan Mewarnai Menggunakan Cat Akrilik Diberbagai Benda - Kusuma, Heru (MITRA: Jurnal Pemberdayaan Masyarakat, 2024)
Paint is a product in the form of liquid or powder which contains coloring substances, and when applied to the surface of an object it forms a layer which has the function of protection, decoration or a special function that is technically required. Visual elements in drawing shape are basic guidelines for draftsman. If the draftsman understands the visual elements in drawing then the image created will be more understandable and in accordance with the drafter’s wishes. Aesthetics as an experience and knowledge becomes a form that is understood as the value of beauty, knowledge of beauty and the beauty of form from an observation of form becomes a beauty. Acrylic paint is a pigment that was first created in the early 20th century by German chemist and entrepreneur Otto Röhm. The first time acrylic paint was available to the general public was in the 1950s. This resin has a wide range of properties, such as excellent water resistance, and exceptional durability when dry, which makes it a perfect material for paint. Coloring activities aim to train skills, neatness and patience. Effective coloring techniques involve mixing colors and knowing contrasting (bright) colors, how to make gradations and shading techniques. From coloring training using acrylic paint, participants already know te 5 pigment-based primary colors and understand various color compositions. Participants are able to mix primary colors to produce secondary colors. Participants are able to color objects from various materials from which they are made. Participants are also able to apply color compositions. Participants are also able to apply color compositions according to their wishes and inspiration.